Bifunctional rice husk-derived SiO2-Cu-Al-Mg nanohybrid catalyst for one-pot conversion of biomass-derived furfural to furfuryl acetate. (1st September 2020) - Hashim, Luqman H.; Halilu, Ahmed; Sudarsanam, Putla; Umar, Yahaya Balarabe; Johan, Mohd Rafie Bin; Bhargava, Suresh K.
Graphical abstract: Highlights: A bifunctional rice husk SiO2 -Cu-Al-Mg catalyst was synthesized. Mg significantly modified the acid-redox properties of RHSiO2 -Cu-Al catalyst. RHSiO2 -Cu-Al catalyst showed good activity in one-pot synthesis of furfuryl acetate. Reaction temperature played a key role in tuning product selectivity. Abstract: Developing one-pot reaction methodologies, which typically require multifunctional catalyst systems, is crucial for sustainable production of bio-derived fuels and chemicals. This work reports one-pot hydrogenation-esterification of furfural to furfuryl acetate using a bifunctional metal-based nanohybrid catalyst, composed of rice husk (RH) derived SiO2, Cu, Al, and Mg species (RHSiO2 -Cu-Al-Mg). For comparison, the catalytic efficiency of RHSiO2 -Cu and RHSiO2 -Cu-Al were tested under similar reaction conditions. Various analytical techniques were used to elucidate the physicochemical, textural, and acid-redox properties of the catalysts. It was found that the RHSiO2 -Cu-Al-Mg catalyst contains an optimum amount of acid and redox sites, as illustrated by NH3 -TPD and H2 -TPR studies, respectively. Especially, Mg addition played a vital role in tailoring acidity of the RHSiO2 -Cu-Al catalyst to promote in-situ esterification of furfuryl alcohol with acetic acid to yield furfuryl acetate. As a result, the RHSiO2 -Cu-Al-Mg catalyst exhibited the best performance in one-pot conversion of furfural to furfuryl acetate, outperforming various noble metal/silica based catalysts. This study offers potential opportunities for the rational design of novel, bifunctional heterogeneous catalysts for efficient production of bio-derived fuels and value added chemicals.